The Role of Discipline in Forming the Performance of the Doctor in Responsibility for Service (DPJP): Systematic Review - Rusyandini Perdana Putri (GLOBAL HEALTH SCIENCE GROUP, 2025)
Optimal healthcare in hospitals relies heavily on the discipline and work quality of health professionals, crucial factors for patient experience and facility reputation, as supported by Indonesian regulations like Law No. 17 of 2023. The Doctor in Charge of Services (DPJP) plays a central role in coordinating patient care and upholding discipline within the medical team. Previous studies confirm the significant impact of work discipline on hospital employee performance. However, factors like poor communication between doctors and patients, identified as a primary cause of disciplinary violations by the Indonesian Medical Discipline Honor Council (MKDKI), also affect service quality. Challenges in Indonesia, such as resource scarcity and high workload, add complexity to the relationship between DPJP discipline and performance.Objective : This study regularly reviews literature from 2021-2025 to explore the role of discipline in shaping DPJP performance, identifying influencing factors and research gaps, aiming to enhance healthcare quality in Indonesia through optimizing DPJP roles.Method : A systematic review, conducted following the PRISMA framework, identified 20 articles out of an initial 1,348 that met the pre-defined inclusion criteria. These articles, published between 2021 and 2025, were retrieved from IJHPM, PubMed, ResearchGate, ScienceDirect, and Springer, with a specific focus on discipline and healthcare professional performance. The PEO framework guided the article search and selection process.Results : Discipline in healthcare management and professional learning positively influences efficiency, effectiveness, and competence. While compensation can boost discipline and performance, unrealistic targets and poor communication can hinder it. Systemic issues also affect discipline and performance.Conclusions : Discipline is vital for DPJP performance and overall healthcare quality, alongside communication and management effectiveness. Optimizing the DPJP role through improved discipline is crucial for enhancing healthcare in Indonesia.